Cost-effectiveness of metacognitive therapy for cardiac rehabilitation participants with symptoms of anxiety and/or depression: analysis of a randomised controlled trial - David Reeves; Calvin Heal; Patrick Joseph Doherty; Gemma E Shields; Adrian Wells; Lora Capobianco; Anthony Heagerty; Deborah Buck; Linda M Davies; Elizabeth Camacho (BMJ Open)
Objectives The burden of cardiovascular disease (CVD) is increasing. Cardiac rehabilitation (CR) is a complex intervention offered to patients with CVD, following a heart event, diagnosis or intervention, and it aims to reduce mortality and morbidity. The objective of this within-trial economic evaluation was to compare the cost-effectiveness of metacognitive therapy (MCT) plus usual care (UC) to UC, from a health and social care perspective in the UK.Methods A multicentre, single-blind, randomised controlled trial (ISRCTN74643496) was conducted in the UK involving 332 patients with CR with elevated symptoms of anxiety and/or depression and compared group-based MCT with UC. The primary outcome of the cost-effectiveness analysis was quality-adjusted life-years (QALYs). The time horizon of the primary analysis was a 12-month follow-up. Missing data were imputed using multiple imputation. Uncertainty was explored by probabilistic bootstrapping. Sensitivity analyses tested the impact of the study design and assumptions on the incremental cost-effectiveness ratio.Results In the primary cost-effectiveness analysis, MCT intervention was dominant, with a cost-saving (net cost −£219; 95% CI −£1446, £1007) and QALY gains (net QALY 0.015; 95% CI −0.015, 0.045). However, there is a high level of uncertainty in the estimates. At a threshold of £30 000 per QALY, MCT intervention of around 76% was likely to be cost-effective.Conclusions Results suggest that intervention may be cost-saving and health-increasing; however, findings are uncertain and subject to limitations. Further research should aim to reduce the uncertainty in the findings (eg, with larger sample sizes) and explore potential longer-term economic benefits associated with MCT in this setting.